Broken Spinal Needle in a Morbidly Obese Parturient Presenting for Urgent Cesarean Section. (30th September 2020) - Shah, Saurin J.; Vanderhoef, Kristen; Ibrahim, Michael
Abstract : Neuraxial anesthesia has become the preferred method of anesthesia for nonemergent cesarean delivery and cases where regional anesthesia is not contraindicated. Multiple cases of broken spinal and epidural needles have been reported in the literature over the last several years; however, the specific incidence of needle breakage is still unknown. Less reliance on general anesthesia and increasing parturient body mass index (BMI) has likely contributed to more reports of broken needles during regional anesthesia for obstetric surgery. We describe a case of a broken spinal needle after attempted spinal anesthetic placement for cesarean delivery in a morbidly obese parturient, subsequent postoperative management, and current treatment recommendations.